1993
DOI: 10.1007/bf02441981
|View full text |Cite
|
Sign up to set email alerts
|

Effect of compliance on a time-domain estimate of the characteristic impedance of the pulmonary artery during acute pulmonary hypertension

Abstract: In 11 pigs under general endotracheal anaesthesia, the time-domain method of determining the pulmonary arterial input impedance was compared with the frequency-domain equivalent under normal conditions as well as acute pulmonary hypertension induced by glass microspheres. The time-domain methods of determining the pulmonary arterial compliance C and pulmonary vascular bed resistance Rp compared favourably with the frequency-domain equivalents (r = 0.774, n = 60, p < 0.001 and r = 0.906, n = 60, p < 0.001, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Moreover, pressure waveform analysis performed in the time domain makes it possible to calculate the timing and extent of wave reflection in systemic and pulmonary circulation with measures such as augmentation index (as shown in Figure 3D), which roughly represents reflected wave summation (⌬P) in the pulmonary circuit and normalizes for the PA pulse pressure. [32][33][34][35][36][37][38][39][40] These values can be obtained easily at the time of right heart catheterization, and future studies will compare both analyses as potential prognostic indicators in patients with pulmonary hypertension and correlate with the previously described concept of capacitance. 41 …”
Section: Time-domain Analysis Of Pa Pressure Waveformsmentioning
confidence: 99%
“…Moreover, pressure waveform analysis performed in the time domain makes it possible to calculate the timing and extent of wave reflection in systemic and pulmonary circulation with measures such as augmentation index (as shown in Figure 3D), which roughly represents reflected wave summation (⌬P) in the pulmonary circuit and normalizes for the PA pulse pressure. [32][33][34][35][36][37][38][39][40] These values can be obtained easily at the time of right heart catheterization, and future studies will compare both analyses as potential prognostic indicators in patients with pulmonary hypertension and correlate with the previously described concept of capacitance. 41 …”
Section: Time-domain Analysis Of Pa Pressure Waveformsmentioning
confidence: 99%
“…Moreover, pressure waveform analysis performed in the time-domain makes it possible to calculate the timing and extent of wave reflection in systemic and pulmonary circulation using measures such as augmentation index (as shown in the Figure) which roughly represents reflected wave summation (∆P) in the pulmonary circuit and normalizes for pulmonary arterial pulse pressure. [15][16][17][18][19][20][21][22][23] These values can be easily obtained at the time of right heart catheterization and the future studies will compare both analyses as potential prognostic indicators in patients with pulmonary hypertension. 24 Right ventricular pressure volume loop relations.…”
Section: Novel Hemodynamic Techniquesmentioning
confidence: 99%
“…They observed a strong correlation between the two estimates, which lead them to conclude that the time domain estimates of Zc are adequate if no other features of the input impedance spectrum are of interest. These results were contrasted in a study by Fourie & Coetzee (1993), who showed that time and frequency domain approaches yield different estimates of Zc.…”
Section: Introductionmentioning
confidence: 70%
“…Thus it is not possible to analytically prove the equivalence of the two approaches. For this reason the ability of each method, in both domains, to produce quantitatively consistent results on a case by case basis remains an open question (Fourie & Coetzee 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation